Native Language in Bilingual Acquisition: Focus on the Mechanisms of Erosion - Krupa-Kwiatkowski, Magdalena (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1997)
This paper focuses on the social mechanisms of erosion of the native language in bilingual acquisition and describes the process of taking over by the new language of the interactional functions previously performed by L1. The paper presents the results of a longitudinal, ethnographic case study of a Polish child learning English as a second language in the context of free play interactions with Polish bilingual and American monolingual children. A dual data base, consisting of the record of the children's speech and behavior and of the record of their interpersonal dynamics as interpreted by the mother, was used in this study for the purpose of extracting patterns of change in the social orientation of the child related to language loss. Each verbal and nonverbal act in the child's behavior that was identified by the mother as related to power negotiation was further described in terms of power position, power stance, and strategic intention adopted by the child. The relation between the child's power orientation and the interactional channel he employed, with special focus on the native language, was statistically evaluated across time.